Experimental Investigation of Natural Circulation Stability Phenomena in a New Loop Heat Pipe Model - Wirza, Alif Rahman; Kusuma, Mukhsinun Hadi; Rozi, Khoiri; Kiono, Berkah Fajar Tamtomo; Restiawan, Mika Ramadhani; Giarno; Pambudi, Yoyok Dwi Setyo; Yunus, Muhammad; Butarbutar, Sofia Loren; Hatmoko, Sumantri; et al. (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2026)
The severe accident at the Fukushima Dai-ichi Nuclear Power Plant in Japan in 2011 highlighted the critical need for a passive cooling system to dissipate residual decay heat following the failure of active cooling systems in the nuclear facility. The loop heat pipe (LHP) is a promising technology for such applications. The objective of this research is to understand the natural circulation stability phenomena of new LHP model under various conditions of filling ratio and heat load. The experimental methodology employed a laboratory-scale LHP model made of copper with an inner diameter of 0.104 m. The experiments were designed with filling ratios of 20%, 40%, 60%, 80%, and 100%, and hot water temperature as the evaporator heat source with variations of 60 °C, 70 °C, 80 °C, and 90 °C. The initial operating pressure was 10665.6 Pa, with a 5˚ inclination angle, demineralized water as the working fluid, and cooled by air at a velocity of 2.5 m/s. The results show that LHP natural circulation happens in two phases and stays stable. The best performance was seen at 90 °C and an 80% filling ratio. The conclusion of this research indicates that natural circulation stability in LHP operates well and occurs in two phases. This demonstrates that LHP effectively acts as a heat absorber and heat dissipator.